CONCEPT OF THE CLOUD INFORMATION SPACE OF EXECUTIVE BODIES OF REGION - Vladimir F. Minakov; Oleg S. Lobanov (Статистика и экономика)
The article discusses the features of building theInformation Space of St. Petersburg. It was statedthat there is strong inefﬁciency of investments inthe existing information systems in St. Petersburg.The reinvention of information systems into cloudservices with private partnership is recommended.Basing on the developed method was provided anapproach to the task of building an effective infrastructure of information systems and the choice ofoptions for its cooperation. The results can be used as a tool for transforming the variety of informationsystems into a single information environment, andtransforming the infrastructure to cloud technologyby reinvention of existing information and telecommunication infrastructure.